PENERAPAN METODE FONIK UNTUK GAME EDUKASI PENYANDANG DISLEKSIA MENGGUNAKAN VISUAL NOVEL - Hasanuddin Hasanuddin (Fakultas Ilmu Komputer, Unversitas Muhammadiyah Riau, 2019)
Multimedia that can help dyslexic children. Visual Novel is an interactive based game that displays stories in the form of static images, and is equipped with conversation boxes to convey narratives and sayings of each character, and sometimes each character has a sound effect so that every character in Visual Novel seems to be alive and able to speak. The method used in making this game is multimedia development life circle, and for the game itself, the phonics method will be used. As for the background of this writing, there is no Indonesian visual novel that has become a learning medium for children with dyslexia. And also visual novel is recommended to be used as a learning media, because it can help children enjoy the learning contained in it.